Identidade profissional do pedagogo, professor do curso de pedagogia - Ferron, Maria Carolina de Sousa (2014)
The issues of professional identity and vocational training area frequently discussed subject nowadays (DUBAR, 2005, 2009; TARDIF, 2012). In the field of Education, is no different (PLACCO; SOUZA, 2005; MARCELO, 2009). In regards to that, the interest in knowing who the teacher, the professor of pedagogy is appeared and who still chooses teaching apart from all the depreciation faced by the professionals from this area. This study aimed to identify how this teacher identity construction occurs, ie, how he became the professional he is today. In this sense, it has become pertinent to check why one chooses this profession, what motivates one to stay on it and why that even with such devaluation. For this, besides the literature about professional identity, teacher education and the history of pedagogy courses in Brazil, semistructured interviews were conducted with three teachers. The data was analyzed and organized into five categories that relate to the goals of there search. Much of the actions of these professionals today as teachers are implied in their personal stories, the way they have perceived school and how they have learned since childhood. The anguish, the learning, the knowledge that should have built their modes of being and acting and transform them on a daily basis into the professional they are today. The commitment to education does not make them give up their profession, even with such devaluation. We further note that, in order to become qualified as a teacher trainer of teachers, it is important to highlight the continuing education, always seeking new knowledge, and giving special importance to theoretical knowledge. Teacher development will never seize to exist, and it is seen as a lifelong learning. Most importantly, the formation is built by means of a work of critical reflection on practice. To constitute the professionals they are today, it is important to emphasize the importance that other teachers had in the lives as respondents, and this happens because the OTHER makes a difference, interfering with the constitution of their identities. Believing in education, liking what you do and realizing its importance in the constitution of the other, are important aspects to become a teacher trainer